2017
DOI: 10.1097/dbp.0000000000000369
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Sleep Duration and Regularity with Dietary Intake Among Preschool-Aged Children with Obesity from Low-Income Families

Abstract: Objective Diet is a modifiable factor associated with pediatric obesity outcomes, but few studies have evaluated the relationships of sleep duration and regularity on dietary intake of young preschool-aged children. The goal of this study was to evaluate whether short sleep duration and irregular sleep timing were associated with greater calorie, carbohydrate and fat consumption among young children with obesity from low-income families. Methods Fifty-one, ethnically diverse children, aged 2-4 years old were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 54 publications
2
29
1
Order By: Relevance
“…In a multiethnic cohort of 2-4 year old children, obese children with poor sleep duration (defined as less than 11 hours of sleep per night), had significantly higher intakes (g/d) of fat and saturated fat as well as a higher percentage of their overall dietary intake (% of kcal) from fat and significantly lower percent calories from carbohydrate during the weekdays. 30 We found that the relationship between the health behaviors and obesity was no longer significant in our model 3 with the inclusion of sleep duration, suggesting that sleep may be an important mechanism linking health behaviors to obesity. Although these findings suggest that sleep mediates the relationship between health behaviors and obesity it is also possible that lack of sleep can have a negative impact on health behaviors which in turn impact obesity.…”
Section: Discussionmentioning
confidence: 59%
“…In a multiethnic cohort of 2-4 year old children, obese children with poor sleep duration (defined as less than 11 hours of sleep per night), had significantly higher intakes (g/d) of fat and saturated fat as well as a higher percentage of their overall dietary intake (% of kcal) from fat and significantly lower percent calories from carbohydrate during the weekdays. 30 We found that the relationship between the health behaviors and obesity was no longer significant in our model 3 with the inclusion of sleep duration, suggesting that sleep may be an important mechanism linking health behaviors to obesity. Although these findings suggest that sleep mediates the relationship between health behaviors and obesity it is also possible that lack of sleep can have a negative impact on health behaviors which in turn impact obesity.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, these preschoolers continued to consume more energy and fat following a night of recovery sleep, suggesting that despite obtaining additional sleep on a subsequent night, the impact of reduced sleep on diet persisted . Similarly, short sleep duration as reported by parents of preschool children was associated with greater fat intake but decreased carbohydrate consumption . Additional research is needed to better understand the impact of insufficient sleep on dietary intake, as well as potential benefits of extended sleep on dietary behaviours in preschool children.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, short sleep duration as reported by parents of preschool children was associated with greater fat intake but decreased carbohydrate consumption. 36 Additional research is needed to better understand the impact of insufficient sleep on dietary intake, as well as potential benefits of extended sleep on dietary behaviours in preschool children.…”
Section: Association Of Insufficient and Late Sleep And Dietary Intakementioning
confidence: 99%
“…Short sleep duration has been associated with obesity in children and adolescents . Few studies have documented this association among preschoolers (3 to 5 years), even though sleep problems and short sleep durations might be common among them and could persist to school age . The US National Sleep Foundation recommends between 10 and 13 hours of sleep per night among preschoolers aged 3 to 5 years .…”
Section: Introductionmentioning
confidence: 99%